Time Resolution Studies of Thallium Based Cherenkov Semiconductors - Terragni, Giulia; Pizzichemi, Marco; Roncali, Emilie; Cherry, Simon R.; Glodo, Jaroslaw; Shah, Kanai; Ariño-Estrada, Gerard; Auffray, Etiennette; Ghezzi, Alessio; Kratochwil, Nicolaus (Frontiers in Physics, 2022)
In the context of improving the detector performance of time-of-flight positron emission tomography (TOF-PET), the combination of charge induction readout and prompt Cherenkov photon production in semiconductor materials can lead to an outstanding detector performance in energy, timing and spatial resolution. Energy resolutions as good as 1.2% at 662 keV and 5% at 122 keV are reported for pixel thallium bromide (TlBr) detectors. The high refractive index of Tl-based materials, between 2.3 and 2.6, leads to a high Cherenkov photon generation yield, but can also challenge photon extraction, potentially affecting the time performance. In this work, the timing properties of TlBr and thallium chloride (TlCl) crystals of different geometries are measured using an optimised test setup with high-frequency readout electronics. A coincidence time resolution (CTR) value of 167 ± 6 ps FWHM is achieved using a 3 x 3 x 3 mm^3 black painted TlBr crystal. In order to assess potential improvements, a Geant4-based simulation toolkit is developed and validated against experimental measurements. The simulation toolkit is used to predict the contributions limiting the time resolution regarding the crystal and photodetector properties, highlighting the potential of such materials. Finally, paths to further improve the detector performance in TOF-PET are discussed.